Self-Disclosure Pengguna Gay di Bumble: Strategi dan Dampaknya terhadap Identitas Seksual dalam Konteks Teori Penetrasi Sosial - Marshella Widjaja; Zera Edenzwo Subandi (Jurnal Ilmu Sosial dan Ilmu Politik (JISIP), 2025)
Online dating apps such as Bumble are becoming increasingly popular among gay individuals looking for partners. However, the process of self-disclosure in the digital space remains a challenge in a society rife with stigma such as Indonesia. This study aims to understand the self-disclosure strategies of gay individuals on Bumble and the challenges they face. Using a qualitative approach with a case study method, this study will explore the subjects' experiences in depth. Data was collected through in-depth interviews with four active informants on Bumble and one gender studies academic. Non-participatory observation and documentation were also used to supplement the data, providing a broader contextual understanding. The analysis uses the theories of Computer-Mediated Communication and Social Penetration. The results show that self-disclosure is done gradually and cautiously, starting with basic information on public profiles, then continuing to more personal conversations on other platforms such as WhatsApp. Although Bumble offers inclusive features such as profile flexibility and gender identity options, users are still hampered by social norms and concerns about discrimination. The study also found that physical beauty standards, masculinity stereotypes, and discrimination against feminine expressions are barriers to openness. Feedback from potential partners also influences the extent to which a person is open. Feedback from potential partners also influences the extent to which a person is open. In addition, this application is not only used to find partners, but also as a space for exploration and validation of identity. This study emphasizes the importance of a safe, inclusive, and empathetic platform design to support the experience of LGBTQ+ users in communicating more freely and reflectively.Aplikasi kencan daring seperti Bumble semakin populer di kalangan individu gay untuk mencari pasangan. Namun, proses keterbukaan diri di ruang digital tetap menjadi tantangan dalam masyarakat yang sarat stigma seperti Indonesia. Penelitian ini bertujuan memahami strategi self-disclosure individu gay di Bumble serta tantangan yang mereka hadapi. Menggunakan pendekatan kualitatif dengan metode studi kasus, penelitian ini akan menggali pengalaman subjek secara mendalam. Data dikumpulkan melalui wawancara mendalam dengan empat Informan aktif di Bumble dan satu akademisi kajian gender. Observasi non-partisipatif dan dokumentasi juga digunakan untuk melengkapi data, memberikan pemahaman kontekstual yang lebih luas. Analisis menggunakan teori Komunikasi Terkomputerisasi dan Penetrasi Sosial. Hasil penelitian menunjukkan bahwa self-disclosure dilakukan secara bertahap dan hati-hati, dimulai dengan informasi dasar di profil publik, lalu berlanjut ke percakapan lebih pribadi di platform lain seperti WhatsApp. Meskipun Bumble menawarkan fitur inklusif seperti fleksibilitas profil dan opsi identitas gender, pengguna tetap terhambat oleh norma sosial dan kekhawatiran akan diskriminasi. Penelitian juga menemukan bahwa standar kecantikan fisik, stereotip maskulinitas, dan diskriminasi terhadap ekspresi feminin menjadi penghalang bagi keterbukaan. Umpan balik dari calon pasangan juga mempengaruhi sejauh mana seseorang terbuka. Selain itu, aplikasi ini tidak hanya digunakan untuk mencari pasangan, tetapi juga menjadi ruang untuk eksplorasi dan validasi identitas. Penelitian ini menekankan pentingnya desain platform yang aman, inklusif, dan empatik untuk mendukung pengalaman pengguna LGBTQ+ dalam berkomunikasi secara lebih bebas dan reflektif.